Measurement of temperature difference on catalyst layer surface under rib and channel in PEFC using micro sensors. (October 2020) - Otsuki, Yota; Shigemasa, Kaito; Araki, Takuto
Highlights: Originally developed 7 µm thickness temperature sensors were used. In-situ local temperature difference between under the rib and channel was measured. Significant effect of dry and wet environment on in-plane temperature distribution. Abstract: Understanding the temperature distribution inside the polymer electrolyte fuel cell (PEFC) during power generation is essential for improving its performance. An originally developed thin-film temperature sensor was used and the measurements of the local temperature in the catalyst layer (CL) and micro porous layer (MPL) interface under the rib and channel were performed for the first time. Results showed that the dry and wet environment inside the cell had a significant effect on the in-plane temperature distribution. The temperature under the rib was lower than the temperature under the channel while supplying 80% relative humidity (RH) gas. Meanwhile, the temperature under the channel was lower than the temperature under the rib in the low current density region when dry gas was supplied. The results of this study could be used to design the components and flow field and optimize the operating conditions such as gas flow rate and humidification.